2014
DOI: 10.1007/s12038-014-9451-y
|View full text |Cite
|
Sign up to set email alerts
|

Does malaria epidemiology project Cameroon as ‘Africa in miniature’?

Abstract: Cameroon, a west-central African country with a ~ 20 million population, is commonly regarded as 'Africa in miniature' due to the extensive biological and cultural diversities of whole Africa being present in a single-country setting. This country is inhabited by ancestral human lineages in unique eco-climatic conditions and diverse topography. Over 90 percent Cameroonians are at risk of malaria infection, and ~ 41 percent have at least one episode of malaria each year. Historically, the rate of malaria infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 67 publications
5
21
1
Order By: Relevance
“…Molecular analysis further confirmed this [49]. The finding of P. falciparum as the sole cause of malaria in the target population is contrary to studies that have reported other Plasmodium species causing malaria including P. vivax [24, 50]. These discrepancies could be attributed to differences in the study designs; our study targeted febrile children presenting to hospitals in the different study sites meanwhile theirs targeted asymptomatic adults and children.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Molecular analysis further confirmed this [49]. The finding of P. falciparum as the sole cause of malaria in the target population is contrary to studies that have reported other Plasmodium species causing malaria including P. vivax [24, 50]. These discrepancies could be attributed to differences in the study designs; our study targeted febrile children presenting to hospitals in the different study sites meanwhile theirs targeted asymptomatic adults and children.…”
Section: Discussionsupporting
confidence: 61%
“…The epidemiology of malaria in Cameroon has been described as unique, having all the different epidemiological strata present in all of Africa [24, 25]. Six epidemiological strata have been identified and mapped in Cameroon namely: the Sudano-sahelian strata, High inland plateau strata, Savannah-forest transmission strata, South Cameroon Equatorial forest strata, High western plateau altitude strata, and the Coastal strata [25].…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, malaria accounts for 48% of all hospital admissions, 30% of morbidity and 67% of childhood mortality per year [5, 6]. The epidemiology of malaria in Cameroon has been described as unique, having all the different epidemiological strata present in all of Africa [7, 8]. Six epidemiological strata have been identified and mapped in Cameroon, namely, the Sudano-sahelian (SS) strata, High inland plateau (HIP) strata, Savannah-forest transmission (SF) strata, South Cameroon Equatorial forest (SCEF) strata, High western plateau altitude (HWP) strata and Coastal (C) strata [7].…”
Section: Introductionmentioning
confidence: 99%
“…[10] Malaria accounts for 26% of work absences and 40% of household health expenses. [11] Due to gender inequalities, low education and socio-economic status resulting from patriarchal structures, more women are trapped in a cycle of poverty, thereby compounding their susceptibility to infections.…”
Section: Introductionmentioning
confidence: 99%